Nghiên cứu tổng hợp biodiesel từ nguyên liệu dầu vi tảo bằng phản ứng ở áp suất cao, sử dụng xúc tác axit - Thành, Nguyễn Trung; Diễn, Lê Quang; Diệu Hồng, Nguyễn Khánh (Vietnam Journal of Chemistry, 2016)
This paper presents the results of study on synthesis of biodiesel from microalgae oil typed Botryococcus by one-stage reaction, with using acid catalysis system SO42-/ZrO2. The maximum yield of biodiesel was 94.5 % at the optimal reaction conditions which have been established as follows: catalytic dosage of 3 % of oil, methanol:oil ratio of 2:1, reaction temperature of 110 oC, reaction time of 180 mins. The chemical composition of obtained biodiesel was analyzed by GC-MS, which showed the identified methyl esters of obtained biodiesel were original from fatty acid radicals of microalgae oil. The physicochemical properties and specifications of synthetic biodiesel were compared with the national standard parameters for B100 biodiesel. The synthetic biodiesel can be used to blend with mineral diesel to create a diesel fuel. Keywords. Biodiesel, acid catalyst, microalgae oil, Botryococcus